Lung function changes over 8 years and testosterone markers in both sexes: UK Biobank. Issue 3 (28th September 2020) - Lenoir, Alexandra; Fuertes, Elaine; Gómez-Real, Francisco; Leynaert, Benedicte; van der Plaat, Diana A.; Jarvis, Debbie
Higher levels of testosterone have been associated with better lung function in cross-sectional population-based studies. The role of testosterone in lung function in women and in lung function decline in men or women is unclear. We studied 5114 men and 5467 women in the UK Biobank with high-quality spirometry at baseline (2006–2010) and 8.4 years later. We studied cross-sectional associations of total testosterone (TT), calculated free testosterone (cFT), free androgen index (FAI) and sex hormone-binding globulin (SHBG) with forced expiratory volume in 1 s (FEV1 ), forced vital capacity (FVC) and FEV1 /FVC using linear regression and associations of baseline markers with lung function decline using linear mixed-effects regression. Men with higher levels of TT had higher FEV1 (27.56 mL per interquartile range increase TT, 95% CI 5.43–49.68) and FVC (48.06 mL, 95% CI 22.07–74.06) at baseline. Higher cFT levels were associated with higher FEV1 and FVC among physically active men only. In women, higher FAI and cFT levels were associated with lower lung function at baseline and higher levels of TT, cFT and FAI were associated with slightly attenuated FEV1 and FVC decline. Higher levels of SHBG were associated with better lung function in both sexes but slightly accelerated decline in men. In this population-based sample, higher levels of TT were associated with better lung function in men and higher levels of cFT with better lung function in physically active men. A small attenuation of lung function decline with higher levels of TT, cFT and FAI was seen in women only. Higher levels of testosterone are associated with better lung function in men, especially if physically active, but not in women. A small attenuation of lung function decline with higher testosterone levels is seen in women only. https://bit.ly/382d0xT